Effect of Sex on Biomarker Response in a Mouse Model of the Hematopoietic Acute Radiation Syndrome. Issue 4 (April 2019) - Jones, Jace W.; Alloush, Jenna; Sellamuthu, Rajendran; Chua, Hui Lin; MacVittie, Thomas J.; Orschell, Christie M.; Kane, Maureen A.
Abstract : Abstract: Sex is an important confounding variable in biomarker development that must be incorporated into biomarker discovery and validation. Additionally, understanding of sex as a biological variable is essential for effective translation of biomarkers in animal models to human populations. Toward these ends, we conducted high-throughput targeted metabolomics using liquid chromatography tandem mass spectrometry and multiplexed immunoassay analyses using a Luminex-based system in both male and female mice in a model of total-body irradiation at a radiation dose consistent with the hematopoietic acute radiation syndrome. Metabolomic and immunoassay analyses identified metabolites and cytokines that were significantly different in plasma from naive and irradiated C57BL/6 mice consisting of equal numbers of female and male mice at 3 d after 8.0 or 8.72 Gy, an approximate LD60–70/30 dose of total-body irradiation. An additional number of metabolites and cytokines had sex-specific responses after radiation. Analyses of sham-irradiated mice illustrate the presence of stress-related changes in several cytokines due simply to undergoing the irradiation procedure, absent actual radiation exposure. Basal differences in metabolite levels between female and male were also identified as well as time-dependent changes in cytokines up to 9 d postexposure. These studies provide data toward defining the influence of sex on plasma-based biomarker candidates in a well-defined mouse model of acute radiation syndrome. Abstract : Supplemental digital content is available in the text.